Information and Communication Technology Skills of Undergraduates of University of Ibadan, Nigeria (2020)
As a result of the rapidly increasing permeation of Information and Communication Technology (ICT) in the education sector, ICT skills have become essential for students in ensuring efficacy in the utilization of this technology. Abilities to operate the computer, and use the software and the Internet, efficiently, are essential sets of ICT skills relevant for students to be successful in all areas of the academic landscape. This study, therefore, was designed to examine the ICT skills of undergraduates of University of Ibadan, Nigeria. The descriptive survey design was adopted, while a two-stage sampling procedure was used to select a sample of 328 students. The instruments used were: Undergraduates’ Skills to Operate the Computer (USOC) (α=0.78), Undergraduates’ Skills to Use the Internet (USUI) (α=0.72) and Undergraduates’ Skills to Use Software (USUS) (α=0.73) scales. Data were analyzed using descriptive statistics. Compared to the threshold mean ( =2.50), the level of USOC was found to be high ( =3.55) and the greatest skill was the ‘ability to start up, log on, and shut down a computer’, while the level of USUI was also high ( =3.17), with the greatest skill of ‘ability to send an E-mail’. The USUS was at a low level ( =2.42) and the greatest skill was the ‘ability to use extended word processing features’. Overall, the undergraduates had a high level of ICT skills ( =3.19). The undergraduates of University of Ibadan, Nigeria had a high level of Information and Communication Technology skills. The university management and the students themselves should gear up efforts to sustain these skills to keep up with the rapid pace of development of Information and Communication Technologies.